Overview of Cerebral Palsy in Children - Dias, Edwin; Sonali , S.; Dias, Akshay (Current Practice in Medical Science Vol. 7, 2022)
Cerebral palsy is a group of permanent disorders of the development of movement and posture, causing activity limitations that are attributed to non progressive disturbances that occurred in the developing fetal or infant brain .The risk factors include antenatal, perinatal, postnatal causes like maternal infection,eclampsia, toxoplasmosis ,rubella, twin birth, low birth weight, difficult delivery and head trauma during the first few years of life. About 2% of cases are believed to be due to an inherited genetic cause. According to European data, the average frequency of Cerebral palsy is 2.08 per 1000 live births. The different types of subtypes have been described on the specific problems present as spastic, dyskinetic, ataxic forms. The classification is also done as spastic diplegia, monoplegia, hemiplegia, double hemiplegia based upon body parts involved. The integrated approach is suggested in management of cerebral palsy which involves specially physiotherapy occupational therapy, speech therapy. The treatment strategies need to be functional goal oriented. Muscle tone optimization, prevention of contractures, improvement in positioning and hygiene and provide good handling to reduce abnormal movement patterns, is the key to improve quality of life in cerebral palsy. The multidisciplinary team including the child and family members should be counseled regarding benefits if serial evaluation, early intervention and encouraged to follow treatment planning.